1995
DOI: 10.1038/hdy.1995.114
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in single and double heterozygotes for two partially overlapping inversions in chromosome 1 of the house mouse

Abstract: Recombination frequency, chiasmata and chromatid interference were studied by means of analysis of meiotic configurations in diakinesis and metaphase II in single and double heterozygotes for the partially overlapping inversions In( 1 )lRk and In( 1)1 2Rk in chromosome 1 of the house mouse.Recombination frequency in the inverted regions was decreased in single heterozygotes and increased in the double heterozygotes as compared to normal homozygotes. Chiasmata in the inverted regions in the double heterozygotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Intriguingly, in carriers of a double inversion of chromosome 1 in mice, a reduction of chiasmata has been seen in single heterozygotes but an increase in the double heterozygotes, the latter associated with a reduced strength of interference [83]. In order to provide an adequate explanation in particular for the apparent decrease in strength of interference in the double hetrozygote it would be helpful to obtain additional information on the relation between synapsis [84] and crossovers by way of MLH1 analysis at the Pachytene stage (see section 2).…”
Section: Resultsmentioning
confidence: 99%
“…Intriguingly, in carriers of a double inversion of chromosome 1 in mice, a reduction of chiasmata has been seen in single heterozygotes but an increase in the double heterozygotes, the latter associated with a reduced strength of interference [83]. In order to provide an adequate explanation in particular for the apparent decrease in strength of interference in the double hetrozygote it would be helpful to obtain additional information on the relation between synapsis [84] and crossovers by way of MLH1 analysis at the Pachytene stage (see section 2).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used murine models and produced quite heterogeneous results. Gorlov and Borodin (1995) [ 43 ], for instance, showed that a large inversion had no effect on the global recombination rate. In an earlier study, the same authors had observed a reduction of recombination due to a decrease in the number of chiasmata in the inverted region [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Mouse embryonic fibroblast (MEF) cultures were prepared from 13-day-old embryos derived from DD/c mice (Kruglova et al 2008), designated as dMEF, and from 12-day-old embryos derived from C57BL-I(I)1Rk mice marked by an inversion in chromosome 1 described earlier (Gorlov and Borodin 1995), designated as iMEF. dMEF and iMEF cells were cultured in Dulbecco's modified Eagle's medium (DMEM; Sigma, Germany) containing 10% FBS (Hyclon, Germany) and 100 µg/ml penicillin and streptomycin.…”
Section: Methodsmentioning
confidence: 99%